The invisible Harry Gold : the man who gave the Soviets the atom bomb - Hornblum, Allen M. (Yale University Press, 2010)
A gripping account of the man who gave the USSR the plans for the atom bomb. The subject of the most intensive public manhunt in the history of the FBI, Gold was arrested in May 1950. His confession revealed scores of contacts, and his testimony in the trial of the Rosenbergs proved pivotal.